Penentuan Jumlah Tenaga Kerja Yang Optimal Berdasarkan Waktu Standar Dengan Metode Work Sampling Di Bagian Penggulungan Di PT. PTPN IV - Uun Novalia Harahap; Zaharuddin Zaharuddin; Abdul Azis Syarif; Bagas Sriwanto; Muhammad Rizki Permana (Universitas Harapan Medan, 2022)
PTPN IV is a State-Owned Enterprise (BUMN) engaged in the agro-industry business which manages tea commodities covering 4% of the entire plantation business at PT. PTPN IV needs to determine the optimal number of workers at the rolling station, because there is an imbalance between working time and labor so that there are additions or reductions. The purpose of this study is to determine the amount of standard time, productivity and determine the number of workers to be employed at the rolling station based on standard time. Through this research, the company can determine the number of employees needed by the company to complete its work. This research was conducted from 07.00 WIB to 16.00 WIB for operators working in the rolling section to limit the problems in the research. The research took place in several stages, namely preliminary observation and then continued with determining the number of observations, work sampling observations, data collection, data processing, analysis of results, and conclusions from research results. This research was conducted using the work sampling method. This is done by observing the actions of workers while working, which is then used to measure their work productivity. By knowing the productivity of the operator, we get the standard work time and the number of productive hours to complete the job, then use it to calculate the total work time with the total processing of the enumeration from observations and calculations so that the number of workers who should be employed is known.